Moroccan-African Religious Diplomacy: Prospects and Challenges - Mohammed Lazrak (Yayasan Rumah Peneleh, 2023)
This article is an attempt to shed light on: first, the milestones of this religious diplomacy towards Africa by exploring the tools that help Morocco achieve its geostrategic goals; second, the challenges as well as threats facing this strategy especially those coming from political and ideological rivals like Algeria and Iran; third, this article will tackle the political benefits of this strategy on the both medium and long term. Within the framework of its soft approach in Africa, Morocco has developed, over the last two decades, an unparalleled policy of exporting its experience of being the hub for moderate Islam, to several African countries, such policy falls within an ambitious geostrategic vision that aims at strengthening the Kingdom’s political and economic influence on the African continent especially in its Western hemisphere. Some aspects of Morocco’s new religious policy in Africa are embodied in several initiatives launched so far for the purpose of enhancing the Moroccan-African cooperation in the religious sphere. Yet, there still exist various challenges to this policy, particularly the competition with other religious authorities in North Africa and the Gulf region, which by its enormous financial might and its active charitable networks, has seriously contested the historical spiritual presence of Morocco within a few West African States, notably Saudi Arabia and Iran.